Mobility Restrictions and Alcohol Use during Lockdown: 'A Still and Dry Pandemic for the Many'? - Martina Celidoni; Joan Costa-Font; Luca Salmasi (Institute of Labor Economics (IZA), 2023)
Unexpected mobility disruptions during lockdown during the first wave of COVID-19 became 'tipping points' with the potential to alter pre-pandemic routines sensitive to socialisation. This paper investigates the impact of lockdown exposure on alcohol consumption. We document two findings using information from the Google Mobility Report and longitudinal data from the Understanding Society in the United Kingdom. First, we find a sharp reduction in both actual mobility and alcohol use (consistent with a "still and dry pandemic for the many" hypothesis). However, we document an increase in alcohol use among heavy drinkers, implying a split behavioural response to COVID-19 mobility restrictions based on alcohol use prior to the pandemic. Second, using the predictions of the prevalence-response elasticity theory, we find that the pandemic's reduction in social contacts is responsible for a 2.8 percentage point reduction in drinking among men.
Keywords: I13; I18; 330; mobility; routines; alcohol use; mobility restrictions; lockdown; health behaviours; difference in differences; COVID-19